Pengaruh Kualitas Pelayanan Dan Keluhan Terhadap Kepuasan Pelanggan Air Minum Bersih PDAM (BUMDes) Di Desa Tanarawa Kecamatan Waiblama Kabupaten Sikka - Marianus Oswaldus; Antonius Phillipus K.Gheta; Dimas Realino (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Water is a basic, irreplaceable human need, so its management must be effective, efficient, and sustainable. The Tanarawa Village Government, through the Village-Owned Enterprise (BUMDes), manages the Regional Drinking Water Company (PDAM) to meet the community's clean water needs. However, various obstacles remain, ranging from suboptimal water quality, uneven distribution, and customer complaints. This situation raises questions about the extent to which service quality and complaints influence customer satisfaction at the Tanarawa Village PDAM, Waiblama District, Sikka Regency. This study aims to: (1) describe the service quality of the Tanarawa Village PDAM, (2) identify the types of complaints submitted by customers, and (3) analyze the influence of service quality and complaints on customer satisfaction. The research method used was a descriptive quantitative approach using a survey technique. Data were collected through questionnaires from 30 respondents who were customers of the Tanarawa Village PDAM. Data analysis included validity and reliability tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of the study, based on descriptive analysis, indicate that service quality, complaints, and satisfaction are categorized as